Finite Element Modelling of Cyclic Behaviour of Cold-Formed Steel Bolted Moment-Resisting Connections - Foster, Peter; Abdelal, Gasser; Lim, James B.P.; Hajsadeghi, Mohammad; McCrum, Daniel (Penerbit Universiti Sains Malaysia, 2016)
This paper investigates the accuracy of new finite element modelling approaches to predict the behaviour of bolted moment-connections between cold-formed steel members, formed by using brackets bolted to the webs of the section, under low cycle fatigue. ABAQUS software is used as a modelling platform. Such joints are used for portal frames and potentially have good seismic resisting capabilities, which is important for construction in developing countries. The modelling implications of a two-dimensional beam element model, a three-dimensional shell element model and a three-dimensional solid element model are reported. Quantitative and qualitative results indicate that the threedimensional quadratic S8R shell element model most accurately predicts the hysteretic behaviour and energy dissipation capacity of the connection when compared to the test results.